An analysis of english language teaching and learning research papers published in Scopus Indexed Journals: the structural compliance with C.A.R.S. Model / Chuah Bee Peng - Chuah, Bee Peng (2019)
Publication is an integral aspect of professional requirement and development for those who work in academia. The recent call for a more robust publication effort by the Malaysian institutes of higher education has compelled the academics to realign their professional scope and interests to meet this key performance indicator set by their faculties. This has also initiated a race among the academics to have their research papers published in high quality peer-reviewed publications, namely the ISI and Scopus indexed journals of their respective disciplines. To this end, academics need to keep abreast with the latest codes and conventions set by these journals for their papers to be accepted and published. One of the ways to refine their writing is to model the structure of their papers on the ones that have been published in the indexed journals.